Identifying influential financial stocks using simulation with a two-layer network. Issue 4 (April 2023) - Lin, Shiqiang; Zhang, Hairui
Abstract: Risk spillover from one stock to another tends to create a contagion effect in the stock market. Fire sales due to the overlapping portfolios of mutual funds can amplify the contagion risks, leading to a downward spiral of stock prices. In this paper, we simulate this downward spiral phenomenon for the Chinese financial stocks based on a two-layer network structure and aim to identify the influential financial stocks based on their individual induced systemic risks. Our findings show that stock liquidity and the concentration of funds' holding on stocks play important roles in determining systemically important financial institutions. Our results also confirm the statements of "too-big-to-fail" and "too-interconnected-to-fail" of financial institutions in the Chinese market. Our results show that a more sensitive flow-performance relationship of mutual funds can amplify the contagion risk by 41%. However, the magnitude can be more drastic in a low market liquidity scenario, where the contagion risk is boosted by 160%.